If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -2 + t(t) = 6 + t(t) Multiply t * t 4t + -2 + t2 = 6 + t(t) Reorder the terms: -2 + 4t + t2 = 6 + t(t) Multiply t * t -2 + 4t + t2 = 6 + t2 Add '-1t2' to each side of the equation. -2 + 4t + t2 + -1t2 = 6 + t2 + -1t2 Combine like terms: t2 + -1t2 = 0 -2 + 4t + 0 = 6 + t2 + -1t2 -2 + 4t = 6 + t2 + -1t2 Combine like terms: t2 + -1t2 = 0 -2 + 4t = 6 + 0 -2 + 4t = 6 Solving -2 + 4t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4t = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4t = 6 + 2 4t = 6 + 2 Combine like terms: 6 + 2 = 8 4t = 8 Divide each side by '4'. t = 2 Simplifying t = 2
| 7(-3*-2)=-14 | | 2(x-10)-5=20x-97 | | 4(2x-6)=10x-6 | | 4x=6-5x | | 6x+2=-27-6x | | 2x-1=-5+6x | | -0.3n+1.2=4.8 | | C=8x^2+7x-45 | | -0.3+1.2=4.8 | | -16w-3=13-8w | | 3x^2+3x-15=13-14x | | 3x-9y=-18 | | 5x+4y=-30 | | 8p-9=47 | | 2(x-6)-9=30x-189 | | -x+5y=-13 | | 6w+8=50 | | 3y+4=22 | | -4x-15y=-17 | | x^3-20x-30=0 | | 2x+5=45 | | -[10z-(21z+7)]=7+(10z+0) | | -0.4x+8=-62.4+6x | | 78n^2+60n=0 | | y+5x=-17 | | -12p-5(5-4p)=5(p-2)-6 | | -3x-3y=3 | | -(-8)(5)=2j | | -2-2x=2x-2.5 | | -5=c+9 | | 12-b=16 | | 2d=16 |